NARRATIVE RESEARCH; A RESEARCH DESIGN - Afan Faizin (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The word narrative describes or describes something in a detailed and chronological story. The procedure in narrative research requires the researcher to get the full story of or from the individual who is the subject of one's research. After obtaining data about someone who is the subject of complete knowledge, researchers must describe the data in a narrative. The analysis used in narrative research includes the strategies used by researchers in describing the story chronologically and completely, studies in biographies that portray all life forms of the study subject